2015
DOI: 10.1177/0022034515608187
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Rates and Lifetime Estimations of CAD/CAM All-ceramic Restorations

Abstract: The gathering of clinical data on fractures of dental restorations through prospective clinical trials is a labor-and time-consuming enterprise. Here, we propose an unconventional approach for collecting large datasets, from which clinical information on indirect restorations can be retrospectively analyzed. The authors accessed the database of an industry-scale machining center in Germany and obtained information on 34,911 computer-aided design (CAD)/computer-aided manufacturing (CAM) all-ceramic posterior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 22 publications
7
68
0
7
Order By: Relevance
“…A prospective clinical trial on multilayer Cad-On ® and monolithic lithium disilicate molar crowns showed no technical failures or fractures after 2 years in service [111]. Another statistical survival analysis based on a large dataset from a CAD/CAM milling center showed 8% fractures of zirconia veneered and glass-fused multilayer FPDs over an interval of 3.5 years [112]. However, in the referred study, the glass-fused multilayer was processed differently from what is recommended by Ivoclar for the CAD-On ® technique, as the milling center used a different fusion glass as well as no vibration to assist accommodation of the fusion glass.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A prospective clinical trial on multilayer Cad-On ® and monolithic lithium disilicate molar crowns showed no technical failures or fractures after 2 years in service [111]. Another statistical survival analysis based on a large dataset from a CAD/CAM milling center showed 8% fractures of zirconia veneered and glass-fused multilayer FPDs over an interval of 3.5 years [112]. However, in the referred study, the glass-fused multilayer was processed differently from what is recommended by Ivoclar for the CAD-On ® technique, as the milling center used a different fusion glass as well as no vibration to assist accommodation of the fusion glass.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The clinical studies have confirmed the successful use of ceramics as dental restorative materials . However, due to the considerable variation, it can be challenging to compare outcomes between studies, materials and restoration types.…”
Section: Introductionmentioning
confidence: 99%
“…In the stress‐bearing areas, the preparation design to allow 2‐mm material thickness for the ceramic indirect restoration is essential to resist flexure under loading . Moreover, the lithium disilicate restorations showed better clinical performance than the leucite‐based glass‐ceramic restorations, emphasizing the importance of the microstructure in the fracture resistance . A previous in vitro study using a lithium disilicate ceramic reported that a reduction of 25% to 50% of the standard preparation depth (2 mm) did not impair fracture resistance of the onlay restoration on premolars …”
mentioning
confidence: 99%